Status de saúde cardiovascular ideal associado à pré-eclâmpsia: uma avaliação baseada na identificação de fatores de risco - Teixeira, João Joadson Duarte (2019)
Preeclampsia (PE) and Cardiovascular Diseases (CVD) are responsible for high rates of maternal morbidity and mortality worldwide. The lifestyle modification for the adoption of healthy habits has been considered an important strategy for primary prevention of CVD to be encouraged for pregnant women. This study aimed to evaluate the Ideal Cardiovascular Health (ICH) status of pregnant women associated or not with the development of PE, identifying the Cardiovascular Risk (CR) factors present in pregnant women in the first gestational trimester; and comparing CR factors with risk factors for PE between the groups of pregnant women with and without PE. This was a prospective open cohort, with pregnant women captured in the first trimester of pregnancy and followed until delivery, from April/2018 to June/2019, in Fortaleza-CE, involving three Primary Health Care Units (PHCU) of each regional. Data were collected using a specific form and processed in the Statistical Package for Social Sciences (SPSS) version 24.0, whit logistic regression mode adjusted with R software version 3.5.5. The study was approved by the Research Ethics Committee, no. 2.448.308 opinion, and were fulfilled all legal requirements required by Resolution 466/2012 of the National Health Council. The final sample consisted of 101 participants, of whom 25 developed preeclampsia (24.75%). The mean age was 24.97 years old (SD± 6.35). Most lived with their partner (70.29%), had 9 years of education or more (79.21%), were a housewife (44.55%), had no income or had less than one minimum wage (69, 3%), brown ethnicity (75.25%), natural (63.37%) and resident (100%) in Fortaleza-CE. The factors associated with the development of PE were: family income from 1 to 3 minimum wages (p<0,01), body mass index (BMI) ≥ 25 Kg/m2 (p<0,01) and blood pressure (BP) ≥ 120/80mmHg (p<0,01). The threat of abortion in the logistic model proved to be a protective variable. It was concluded that 9.90% of the sample had ICH status and only BMI and BP influence the outcome of PE with increased cardiovascular risk, corroborating with the need to guide lifestyle changes to prevent CVD in the postpartum period of women who have PE.